Multifunctional organic monolayer-based coatings for implantable biosensors and bioelectronic devices: Review and perspectives - Taral Patel; Jie Huang; Katarzyna Krukiewicz (Biosensors and Bioelectronics: X, 2023)
The emerging field of biosensors and bioelectronics seeks to exploit biology in combination with the recent advances in engineering. Even though biomedical implants can significantly improve quality of life, problems following the process of implantation are still an issue. In this review, we point out organic monolayer-based coatings as a potential solution to the major limitations of implantable biomaterials, including limited biocompatibility, the risk of biofouling, bacterial colonization, and stability under in vivo conditions. At first, selected current and perspective biomaterials are discussed, with the focus on their use as implantable biosensors and biomedical electrodes. Surface modification strategies for implantable biomedical devices are then extensively discussed, with an emphasis on the use of self-assembled monolayers and covalently-attached diazonium/iodonium/sulfonium-based moieties. The development of design concepts for bioelectrodes and biosensors is also highlighted. The last section describes characterization techniques that are particularly useful in studying organic monolayers. It is demonstrated that biomaterials-based tissue engineering technologies can be easily used to construct clinically-driven in vivo biosensors and bioelectronic instruments with outstanding functionality.